(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to evaluate the benefits of continuous periarticular cocktail infusion in total knee replacement patients in terms of pain control and early restoration of knee range of motion after surgery. Methods: A total of 50 patients undergoing unilateral total knee replacement were enrolled and divided into two groups: one group received continuous cocktail infusion into the joint capsule, while the other group received continuous Ropivacaine infusion into the adductor canal. During surgery, all patients were given periarticular injections consisting of Ropivacaine, Ketorolac, Dexamethason, and Epinephrine. Perioperative analgesia protocols were standardized for all patients. Pain scores VAS and knee range of motion were recorded on the day of surgery, postoperative day 1, postoperative day 2, and at discharge. Complications and the need for rescue analgesics were also monitored. Results: Patients in the continuous periarticular cocktail group had a mean VAS score of 0.8 ± 1.5 and showed better functional recovery, with the ability to flex the knee to 90 degrees within 2 days. The requirement for rescue analgesics was significantly reduced at 6 hours, 12 hours, and within the first 24 hours postoperatively. No cases of local anesthetic toxicity or other complications were observed. Conclusion: Continuous periarticular cocktail infusion following intraoperative cocktail injection significantly reduces postoperative analgesic requirements and improves patient satisfaction without increasing complication risks after total knee replacement.